Early childhood language arts - Jalongo, Mary Renck (Unites States of America : Pearson, 2014)
Definition of literacy have extended well beyond the ability to read and write. In response to the rising expectation for early childhood educators effectiveness and students achievement, six significant changes have been made to this edition.
Part One. Language Learning in Context -- Part Two: Oral Language -- Part Three: Literacy with Print -- Part Four: Written Language and Symbol Systems -- Part Five: The Teacher of Language Arts .
Includes bibliographical references and index.
Keywords: LANGUAGE ARTS